Manganese-zinc power ferrite composite material and preparation method thereof
The manganese-zinc power ferrite composite material, with a tailored binder composition and optimized processing, addresses the performance degradation issue caused by organic binders, resulting in high magnetic and mechanical properties for complex, miniaturized magnets.
Patent Information
- Application Number
- CN202411105911.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-13
AI Technical Summary
Existing injection molding processes for manganese-zinc ferrite materials face challenges in achieving high magnetic properties and mechanical strength due to the addition of non-magnetic organic binders, which compromise the overall performance of the magnets.
A manganese-zinc power ferrite composite material is formulated with a specific binder composition comprising polyoxymethylene resin, high-density polyethylene, polyethylene-octene co-elastomer, zinc stearate, and dioctyl phthalate, optimized to improve fluidity, mechanical strength, and magnetic properties, followed by a process involving mixing, extrusion, injection molding, and degreasing.
The composite material achieves high magnetic induction intensity, low power loss, and good mechanical strength, suitable for complex shapes and miniaturized magnetic devices.
Smart Images

Figure CN119143494A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ferrite materials, and in particular relates to a manganese-zinc power ferrite composite material and a preparation method thereof. Background Art
[0002] In recent years, with the vigorous development of the electric power industry, the electronics industry and the automobile industry, various components and equipment have gradually tended to shift towards miniaturization, complexity and diversification. At the same time, the demand for small magnetic devices with high magnetic properties and complex shapes is also increasing.
[0003] Powder metallurgy technology can produce high-performance magnetic components. At present, the traditional dry pressing process has broken through the limitations of existing molding processes. It mainly uses the fluidity of powder to fill the mold and press the parts, but there are certain limitations in the manufacture of complex shapes such as external grooves, horizontal holes, blind holes, external threads, concave platforms, key pins, surface knurling, and parts with numbers or logos. Plastic injection molding technology can mass-produce various complex-shaped products at a low price, but it cannot guarantee high magnetic properties. Injection molding technology has irreplaceable advantages in material molding due to its advantages such as mass production, precise manufacturing dimensions and easy molding.
[0004] Manganese-zinc ferrite materials have excellent characteristics of high frequency, high magnetic permeability, high saturation magnetic induction intensity (Bs) and low power loss (Pc), so they can be widely used in new energy vehicles, medical treatment, communications and other fields. Therefore, in order to meet the needs of diversified product structure and high performance in the future, it is very necessary to develop the injection molding process of manganese-zinc ferrite materials.
[0005] The injection molding process can meet the high-precision requirements of the prepared magnetic device, but due to the presence of a large amount of non-magnetic organic binder components in the raw materials, the magnetic properties of the magnet decrease. Based on this, Chinese invention patent CN111370198A discloses an injection-molded soft ferrite magnet, the specific components of which include: 80-93% soft ferrite magnetic powder, 0.1-1.0% magnetic powder surface modifier, 0.1-0.5% coupling agent, 0.2-0.8% surface organic insulating agent, 6-19% binder and 0.1-1.0% flow aid, thereby preparing a soft ferrite magnet for injection molding with high crush strength, easy molding of complex shapes and miniaturization. However, the overall magnetic permeability of the above-mentioned magnet is low, and other magnetic properties (such as volume power consumption value or saturation magnetic induction intensity, etc.) have not been publicly tested.
[0006] In summary, the present invention aims to utilize injection molding technology to manufacture small complex magnets with high magnetic properties, while solving the technical problem that the overall performance of the magnet is reduced due to the addition of a large amount of organic binder to the above raw materials. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a manganese-zinc power ferrite composite material and a preparation method thereof. In order to solve the technical problems that it is difficult to form a small and complex magnetic core, and the addition of an organic binder causes the magnetic properties of the manganese-zinc power ferrite material to decrease, the present invention improves the injection molding performance of the manganese-zinc power ferrite composite material by adjusting the composition of the binder and improving the process conditions, thereby ensuring that it has high magnetic induction intensity (Bs), low power loss (Pc) and good mechanical strength.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a manganese-zinc power ferrite composite material, wherein the manganese-zinc power ferrite composite material is made of the following components in weight percentage: 75% to 90% of a manganese-zinc power ferrite material and 10% to 25% of a binder composition;
[0010] The adhesive composition is composed of the following components in weight percentage: 10% to 15% of polyoxymethylene resin (POM), 2% to 5% of high-density polyethylene (HDPE), 0.5% to 1.5% of polyethylene-octene co-elastomer (POE), 0.2% to 0.5% of vinyl bisstearamide (EBS), 1% to 3% of zinc stearate (SA) and 1% to 3% of dioctyl phthalate (DOP).
[0011] The present invention improves the injection molding performance, magnetic properties and mechanical strength of the manganese-zinc power ferrite composite material by adjusting the formula of the binder. First, the present invention selects polyoxymethylene resin (POM) as the main component of the binder, which not only has better fluidity, but also has almost no branches and side groups on the POM molecular chain, and most of the carbon atoms are connected to hydrogen atoms, making the molecular chain very regular, so POM has a high degree of crystallinity; at the same time, the carbon-oxygen bonds in the POM molecules are short, so the cohesive energy density of POM is high, and the molecular chains are tightly aggregated. This structure helps to reduce the directionality of the chain during the forming process, thereby obtaining a formed blank with good isotropy. In addition, POM also has the advantages of high mechanical strength, fatigue resistance, creep resistance, wear resistance and good chemical resistance, thereby further improving the mechanical properties and practicality of the manganese-zinc power ferrite composite material.
[0012] Secondly, the present invention uses high-density polyethylene (HDPE) as a stabilizer, so that the material structure can maintain long-term stability and uniform dispersion during subsequent processing, especially maintaining good stability under the action of high shear force.
[0013] In addition, the present invention adopts dioctyl phthalate (DOP) as a plasticizer, which can reduce the glass transition temperature of POM and ultimately increase its heat deformation temperature, so that POM maintains good wettability to the manganese-zinc power ferrite material, thereby improving the miscibility of the manganese-zinc power ferrite material and the binder composition, and ultimately improving the magnetic properties of the manganese-zinc power ferrite composite material.
[0014] Finally, the polyoxymethylene resin component in the adhesive composition provided by the present invention is easily chemically decomposed in the subsequent catalytic degreasing, thereby accelerating the degreasing reaction rate and greatly improving the degreasing efficiency.
[0015] In the present invention, the weight percentage of the manganese-zinc power ferrite material is 75% to 90%, for example, it can be 75%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, etc.
[0016] In the present invention, the weight percentage of the binder composition is 10% to 25%, for example, it can be 10%, 11%, 12%, 13%, 14%, 15%, 18%, 20%, 22%, 25%, etc.
[0017] In the present invention, the weight percentage of the polyoxymethylene resin is 10% to 15%, for example, it can be 10%, 11%, 12%, 13%, 14%, 15%, etc. If the weight percentage is too low, the material cannot be formed by mixing, and on the contrary, if the amount added is too large, the product performance will be reduced and the processing difficulty will be increased.
[0018] In the present invention, the weight percentage of the high-density polyethylene is 2% to 5%, for example, it can be 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5%, etc. Too low a weight percentage will lead to decreased stability and durability of the material, otherwise it will result in uneven kneading.
[0019] In the present invention, the weight percentage of the polyethylene octene co-elastomer is 0.5% to 1.5%, for example, it can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, etc. In the present invention, the weight percentage of the polyethylene octene co-elastomer is controlled to be within the preferred content range. If the weight percentage is too low, the flexibility of the product will be insufficient, and vice versa, the dimensional stability of the product will be affected.
[0020] In the present invention, the weight percentage of the vinyl bisstearamide is 0.2% to 0.5%, for example, it can be 0.2%, 0.22%, 0.25%, 0.28%, 0.3%, 0.32%, 0.35%, 0.38%, 0.4%, 0.42%, 0.45%, 0.48%, 0.5%, etc.
[0021] In the present invention, the weight percentage of the zinc stearate is 1% to 3%, for example, it can be 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, etc.
[0022] In the present invention, the weight percentages of vinyl bisstearamide and zinc stearate are adjusted so that their contents are controlled within a preferred content range. Too low a weight percentage will result in poor lubrication of the product, while too much added may form an overly thick coating on the mold surface, which in turn makes demolding difficult.
[0023] In the present invention, the weight percentage of dioctyl phthalate is 1% to 3%, for example, it can be 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3, etc. Too low a weight percentage will result in poor plasticization effect of the product, and conversely will significantly reduce the mechanical properties of the product such as tensile strength and hardness.
[0024] Preferably, the manganese-zinc power ferrite composite material is made of the following components in weight percentage: 78% to 85% of manganese-zinc power ferrite material and 15% to 22% of a binder composition.
[0025] Preferably, the adhesive composition is composed of the following components in weight percentage: 10% to 14% polyoxymethylene resin, 2% to 3% high-density polyethylene, 1% to 1.5% polyethylene-octene co-elastomer, 0.3% to 0.5% vinyl bisstearamide, 2% to 3% zinc stearate and 1% to 2% dioctyl phthalate.
[0026] Preferably, the average particle size of the manganese-zinc power ferrite material is 1.1-1.4 μm, for example, it can be 1.1 μm, 1.12 μm, 1.15 μm, 1.18 μm, 1.2 μm, 1.21 μm, 1.22 μm, 1.23 μm, 1.24 μm, 1.25 μm, 1.26 μm, 1.27 μm, 1.28 μm, 1.29 μm, 1.3 μm, 1.32 μm, 1.35 μm, 1.38 μm, 1.4 μm, etc.
[0027] Preferably, the melt index of the polyoxymethylene resin is 90-150 g / 10 min, preferably 120 g / 10 min, for example, it can be 90 g / 10 min, 100 g / 10 min, 110 g / 10 min, 120 g / 10 min, 130 g / 10 min, 140 g / 10 min, 150 g / 10 min, etc.
[0028] Preferably, the molecular weight of the high-density polyethylene is 40,000 to 300,000, preferably 100,000, for example, 40,000, 60,000, 80,000, 100,000, 200,000, 300,000, etc.
[0029] Preferably, the melt index of the high-density polyethylene is 0.1-10 g / 10 min, preferably 0.5 g / 10 min, for example, it can be 0.1 g / 10 min, 0.2 g / 10 min, 0.5 g / 10 min, 0.8 g / 10 min, 1 g / 10 min, 2 g / 10 min, 5 g / 10 min, 8 g / 10 min, 10 g / 10 min, etc.
[0030] Preferably, the molecular weight of the polyethylene-octene co-elastomer is 3000-3500, preferably 3500, for example, 3000, 3100, 3200, 3300, 3400, 3500, etc.
[0031] Preferably, the melt index of the polyethylene-octene co-elastomer is 0.1-3 g / 10min, preferably 1.2 g / 10min, for example, it can be 0.1 g / 10min, 0.3 g / 10min, 0.5 g / 10min, 0.8 g / 10min, 1 g / 10min, 1.2 g / 10min, 1.5 g / 10min, 2 g / 10min, 2.2 g / 10min, 2.5 g / 10min, 2.8 g / 10min, 3 g / 10min, etc.
[0032] In the present invention, by adjusting the physical property parameters of the above components, the binder composition has the best performance, which is convenient for improving the injection molding performance, magnetic properties and mechanical strength of the manganese-zinc power ferrite composite material.
[0033] In a second aspect, the present invention provides a method for preparing the manganese-zinc power ferrite composite material according to the first aspect, the method comprising the following steps:
[0034] Mixing and kneading the manganese-zinc power ferrite material and the binder composition according to the formula amount to obtain a first material;
[0035] Extruding and granulating the first material to obtain a second material;
[0036] The second material is subjected to injection molding to obtain a green body;
[0037] Degreasing the green body to obtain a degreased body;
[0038] The degreased blank is sintered to obtain the manganese-zinc power ferrite composite material.
[0039] Preferably, the preparation method of the manganese-zinc power ferrite material comprises the following steps: subjecting iron oxide, manganese oxide and zinc oxide to a ball-milling treatment to obtain a primary ball-milled material; subjecting the primary ball-milled material to a pre-burning treatment to obtain a pre-burned material; subjecting the pre-burned material to a secondary ball-milling treatment to obtain the manganese-zinc power ferrite material.
[0040] Preferably, the mass ratio of the iron oxide, manganese oxide and zinc oxide is 73.4:21.8:4.8;
[0041] Preferably, the pre-sintering treatment is performed at a temperature of 600 to 900° C., for example, 600° C., 700° C., 800° C., 900° C., etc., and the pre-sintering time is 2 to 4 hours, for example, 2 hours, 3 hours, 4 hours, etc.;
[0042] Preferably, the secondary ball milling process further includes drying and screening processes.
[0043] Preferably, the water content of the manganese-zinc power ferrite material is ≤0.1%, for example, it may be 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, etc.
[0044] Preferably, the banburying temperature is 160°C to 190°C, preferably 180°C to 190°C, for example, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, etc.
[0045] Preferably, the banburying time is 30 min to 60 min, preferably 30 min to 45 min, for example, it can be 30 min, 32 min, 35 min, 38 min, 40 min, 42 min, 45 min, 48 min, 50 min, 52 min, 55 min, 58 min, 60 min, etc.
[0046] In the present invention, if the kneading temperature is too low or the kneading time is too long, it will cause the binder composition to wrap the magnetic powder unevenly, thereby reducing the mechanical strength of the manganese-zinc power ferrite composite material.
[0047] Preferably, the temperature of the granulation treatment is 150°C to 170°C, preferably 150°C to 160°C, for example, 150°C, 155°C, 160°C, 165°C, 170°C, etc.
[0048] Preferably, the length of the second material is 3-5 mm, for example, 3 mm, 3.2 mm, 3.5 mm, 3.8 mm, 4 mm, 4.2 mm, 4.5 mm, 4.8 mm, 5 mm, etc.
[0049] Preferably, the temperature of the injection molding process is 80°C to 140°C, for example, 80°C, 85°C, 90°C, 95°C, 100°C, 110°C, 120°C, 130°C, 140°C, etc.
[0050] Preferably, the temperature of the degreasing treatment is 100-200°C, preferably 120-150°C, for example, it can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, etc.
[0051] Preferably, the degreasing treatment uses oxalic acid for degreasing.
[0052] In the present invention, the polyformaldehyde resin in the adhesive composition provided by the present invention is easily chemically decomposed under the action of oxalic acid, and nitrogen plays a protective role in the reaction and takes away the formaldehyde gas produced by the decomposition so that the reaction can continue to occur rapidly, thereby greatly improving the degreasing efficiency.
[0053] Preferably, the oxalic acid feeding amount is 1 to 5 g / min, preferably 1 to 3 g / min, for example, it can be 1 g / min, 1.5 g / min, 2 g / min, 2.5 g / min, 3 g / min, 3.5 g / min, 4 g / min, 4.5 g / min, 5 g / min.
[0054] Preferably, the sintering treatment temperature is 1250°C to 1350°C, for example, it can be 1250°C, 1260°C, 1270°C, 1280°C, 1290°C, 1300°C, 1310°C, 1320°C, 1330°C, 1340°C, 1350°C, etc.; the sintering time is 4 to 12h, for example, it can be 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc.
[0055] Preferably, the volume content of oxygen during the sintering process is 2-21 vol%, for example, it can be 2 vol%, 3 vol%, 5 vol%, 8 vol%, 10 vol%, 12 vol%, 15 vol%, 18 vol%, 20 vol%, 21 vol%, etc.
[0056] Preferably, the sintering process includes first sintering at 1280-1330°C for 5-8h under the condition of an oxygen volume content of 19-21vol%, then sintering at 1280-1330°C for 1-4h under the condition of an oxygen volume content of 2-5vol%, and finally cooling under a balanced oxygen partial pressure.
[0057] Compared with the prior art, the present invention has the following beneficial effects:
[0058] The present invention provides a manganese-zinc power ferrite composite material. First, the present invention selects polyoxymethylene resin (POM) as the main component of the binder, which not only has better fluidity, but also has almost no branches and side groups on the POM molecular chain, and most of the carbon atoms are connected to hydrogen atoms, making the molecular chain very regular, so POM has a high degree of crystallinity; at the same time, the carbon-oxygen bond in the POM molecule is short, so the cohesive energy density of POM is high, and the molecular chain is tightly aggregated. This structure helps to reduce the directionality of the chain during the forming process, thereby obtaining a formed blank with good isotropy. In addition, POM also has the advantages of high mechanical strength, fatigue resistance, creep resistance, wear resistance and good chemical resistance, thereby further improving the mechanical properties and practicality of the manganese-zinc power ferrite composite material.
[0059] Secondly, the present invention uses high-density polyethylene (HDPE) as a stabilizer, so that the material structure can maintain long-term stability and uniform dispersion during subsequent processing, especially maintaining good stability under the action of high shear force.
[0060] In addition, the present invention adopts dioctyl phthalate (DOP) as a plasticizer, which can reduce the glass transition temperature of POM and ultimately increase its heat deformation temperature, so that POM maintains good wettability to the manganese-zinc power ferrite material, thereby improving the miscibility of the manganese-zinc power ferrite material and the binder composition, and ultimately improving the magnetic properties of the manganese-zinc power ferrite composite material.
[0061] Finally, the polyoxymethylene resin component in the adhesive composition provided by the present invention is easily chemically decomposed in the subsequent catalytic degreasing, thereby accelerating the degreasing reaction rate and greatly improving the degreasing efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 A schematic diagram of a magnetic ring sample and a magnetic strip sample of a green body after injection molding provided by the present invention;
[0063] Figure 2 This is a schematic diagram of measuring the compressive strength of a magnetic strip using a universal testing machine. DETAILED DESCRIPTION
[0064] The technical solution of the present invention is further described below by combining the accompanying drawings and specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0065] The preparation method of the manganese-zinc power ferrite soft magnetic material in the embodiments and comparative examples of the present invention comprises the following steps: subjecting iron oxide, manganese oxide and zinc oxide to a ball milling treatment in a mass ratio of 73.4:21.8:4.8 to a primary ball milling treatment to obtain a primary ball milled material; subjecting the primary ball milled material to a pre-burning treatment at 800°C for 3 hours to obtain a pre-burned material; subjecting the pre-burned material to a secondary ball milling treatment, drying and sieving to obtain the manganese-zinc power ferrite soft magnetic material.
[0066] The average particle size (D50) of the manganese-zinc power ferrite soft magnetic material is measured by the Fisher permeability method, and the measuring instrument is the HMK-22 average particle size analyzer.
[0067] The melt index of the polyoxymethylene resin in the embodiments and comparative examples of the present invention is 120 g / 10 min; the molecular weight of the high-density polyethylene is 100,000, and the melt index is 0.5 g / 10 min; the molecular weight of the polyethylene-octene co-elastomer is 3,500, and the melt index is 1.2 g / 10 min.
[0068] Example 1
[0069] The present embodiment provides a manganese-zinc power ferrite composite material, which is made of the following components in weight percentage: 80% of manganese-zinc power ferrite soft magnetic material (average particle size of 1.1 μm, water content ≤0.1%) and 20% of a binder composition; the binder composition is composed of the following components in weight percentage: 12.5% of polyoxymethylene resin, 2.5% of high-density polyethylene, 1.5% of polyethylene-octene co-elastomer, 0.5% of vinyl bisstearamide, 2% of zinc stearate and 1% of dioctyl phthalate.
[0070] This embodiment provides a method for preparing the above-mentioned manganese-zinc power ferrite composite material, which comprises the following steps:
[0071] (1) Banburying: Weigh the components of the binder according to the formula, mix to obtain a binder composition, and mix it with the manganese-zinc power ferrite soft magnetic material; raise the temperature of the banbury mixer to 190° C. for preheating, and add the manganese-zinc power ferrite soft magnetic material and the binder composition in sequence after preheating; first, premix at a speed of 10 r / min and press for 20 min, then increase the speed to 25 r / min and mix for 10 min, then increase the speed to 40 r / min, and banbury and keep warm for 40 min to obtain the first material;
[0072] (2) adding the first material into a granulator, extruding and granulating at 160° C. to obtain a second material having a length of 2-3 mm;
[0073] (3) The second material is subjected to injection molding to form a mold at 80°C. Figure 1 The magnetic ring green body with a size of Φ16mm×Φ9mm×8mm and the magnetic strip green body with a height of 8mm are shown;
[0074] (4) placing the magnetic ring green body and the magnetic strip green body in an oxalic acid degreasing furnace, performing a degreasing treatment at 130° C. and an acid feeding amount of 3 g / min to obtain a degreased green body;
[0075] (5) The debinded blank is first sintered in a nitrogen-oxygen mixed gas (the volume content of oxygen is 21 vol%) at 1290° C. for 6 h, then sintered in a nitrogen-oxygen mixed gas (the volume content of oxygen is 2 vol%) at 1290° C. for 3 h, and finally cooled under a balanced oxygen partial pressure to obtain a manganese-zinc power ferrite magnetic ring composite material and a manganese-zinc power ferrite magnetic strip composite material.
[0076] Example 2
[0077] The present embodiment provides a manganese-zinc power ferrite composite material, which is made of the following components in weight percentage: 78% of manganese-zinc power ferrite soft magnetic material (average particle size of 1.2 μm, water content ≤0.1%) and 22% of a binder composition; the binder composition is composed of the following components in weight percentage: 14% of polyoxymethylene resin, 3% of high-density polyethylene, 1% of polyethylene-octene co-elastomer, 0.5% of vinyl bisstearamide, 2.5% of zinc stearate and 1% of dioctyl phthalate.
[0078] This embodiment provides a method for preparing the above-mentioned manganese-zinc power ferrite composite material, which comprises the following steps:
[0079] (1) Banburying: weighing the components of the binder according to the formula, mixing to obtain a binder composition, and mixing it with the manganese-zinc power ferrite soft magnetic material; raising the temperature of the banbury mixer to 185° C. for preheating, and adding the manganese-zinc power ferrite soft magnetic material and the binder composition in sequence after preheating; first premixing at a speed of 10 r / min and pressing for 20 min, then increasing the speed to 25 r / min and mixing for 10 min, and then increasing the speed to 40 r / min, banburying and heat preservation for 40 min to obtain the first material;
[0080] (2) adding the first material into a granulator, extruding and granulating at 155° C. to obtain a second material having a length of 2-3 mm;
[0081] (3) subjecting the second material to injection molding, and forming a magnetic ring blank with a size of Φ16 mm×Φ9 mm×8 mm and a magnetic strip blank with a height of 8 mm through a mold at 80° C.;
[0082] (4) placing the magnetic ring green body and the magnetic strip green body in an oxalic acid degreasing furnace, performing a degreasing treatment at 130° C. and an acid feeding amount of 3 g / min to obtain a degreased green body;
[0083] (5) The debinded blank is first sintered in a nitrogen-oxygen mixed gas (the volume content of oxygen is 21 vol%) at 1310° C. for 5 h, then sintered in a nitrogen-oxygen mixed gas (the volume content of oxygen is 5 vol%) at 1310° C. for 4 h, and finally cooled under a balanced oxygen partial pressure to obtain a manganese-zinc power ferrite magnetic ring composite material and a manganese-zinc power ferrite magnetic strip composite material.
[0084] Example 3
[0085] The present embodiment provides a manganese-zinc power ferrite composite material, which is made of the following components in weight percentage: 80.5% of manganese-zinc power ferrite soft magnetic material (average particle size of 1.1 μm, water content ≤0.1%) and 19.5% of a binder composition; the binder composition is composed of the following components in weight percentage: 13% of polyoxymethylene resin, 2% of high-density polyethylene, 1% of polyethylene-octene co-elastomer, 0.5% of vinyl bisstearamide, 2% of zinc stearate and 1% of dioctyl phthalate.
[0086] This embodiment provides a method for preparing the above-mentioned manganese-zinc power ferrite composite material, which comprises the following steps:
[0087] (1) Banburying: weighing the components of the binder according to the formula, mixing to obtain a binder composition, and mixing with the manganese-zinc power ferrite soft magnetic material; raising the temperature of the banbury mixer to 185° C. for preheating, and adding the manganese-zinc power ferrite soft magnetic material and the binder composition in sequence after preheating; first premixing at a speed of 10 r / min and pressing for 20 min, then increasing the speed to 25 r / min for mixing for 10 min, and then increasing the speed to 40 r / min, banburying and heat preservation for 30 min to obtain the first material;
[0088] (2) adding the first material into a granulator, extruding and granulating at 155° C. to obtain a second material having a length of 2-3 mm;
[0089] (3) subjecting the second material to injection molding, and forming a magnetic ring blank with a size of Φ16 mm×Φ9 mm×8 mm and a magnetic strip blank with a height of 8 mm through a mold at 80° C.;
[0090] (4) placing the magnetic ring green body and the magnetic strip green body in an oxalic acid degreasing furnace, performing a degreasing treatment at 130° C. and an acid feeding amount of 4 g / min to obtain a degreased green body;
[0091] (5) The debinded blank is first sintered in a nitrogen-oxygen mixed gas (the volume content of oxygen is 21 vol%) at 1310° C. for 5 h, then sintered in a nitrogen-oxygen mixed gas (the volume content of oxygen is 5 vol%) at 1310° C. for 4 h, and finally cooled under a balanced oxygen partial pressure to obtain a manganese-zinc power ferrite magnetic ring composite material and a manganese-zinc power ferrite magnetic strip composite material.
[0092] Example 4
[0093] The present embodiment provides a manganese-zinc power ferrite composite material, which is made of the following components in weight percentage: 77% of manganese-zinc power ferrite soft magnetic material (average particle size of 1.1 μm, water content ≤0.1%) and 23% of a binder composition; the binder composition is composed of the following components in weight percentage: 13% of polyoxymethylene resin, 4% of high-density polyethylene, 1.5% of polyethylene-octene co-elastomer, 0.5% of vinyl bisstearamide, 2.5% of zinc stearate and 1.5% of dioctyl phthalate.
[0094] This embodiment provides a method for preparing the above-mentioned manganese-zinc power ferrite composite material, which comprises the following steps:
[0095] (1) Banburying: Weigh the components of the binder according to the formula, mix to obtain a binder composition, and mix it with the manganese-zinc power ferrite soft magnetic material; raise the temperature of the banbury mixer to 180° C. for preheating, and add the manganese-zinc power ferrite soft magnetic material and the binder composition in sequence after preheating; first, premix at a speed of 10 r / min and press for 20 min, then increase the speed to 25 r / min and mix for 10 min, then increase the speed to 40 r / min, and banbury and keep warm for 30 min to obtain the first material;
[0096] (2) adding the first material into a granulator, extruding and granulating at 155° C. to obtain a second material having a length of 2-3 mm;
[0097] (3) subjecting the second material to injection molding, and forming a magnetic ring blank with a size of Φ16 mm×Φ9 mm×8 mm and a magnetic strip blank with a height of 8 mm through a mold at 80° C.;
[0098] (4) placing the magnetic ring green body and the magnetic strip green body in an oxalic acid degreasing furnace, performing a degreasing treatment at 130° C. and an acid feeding amount of 4 g / min to obtain a degreased green body;
[0099] (5) The debinded blank is first sintered in a nitrogen-oxygen mixed gas (the volume content of oxygen is 21 vol%) at 1290° C. for 5 h, then sintered in a nitrogen-oxygen mixed gas (the volume content of oxygen is 5 vol%) at 1290° C. for 4 h, and finally cooled under a balanced oxygen partial pressure to obtain a manganese-zinc power ferrite magnetic ring composite material and a manganese-zinc power ferrite magnetic strip composite material.
[0100] Example 5
[0101] The present embodiment provides a manganese-zinc power ferrite composite material, which is made of the following components in weight percentage: 80% of manganese-zinc power ferrite soft magnetic material (average particle size of 1.2 μm, water content ≤0.1%) and 20% of a binder composition; the binder composition is composed of the following components in weight percentage: 12.5% of polyoxymethylene resin, 2.2% of high-density polyethylene, 1.5% of polyethylene-octene co-elastomer, 0.3% of vinyl bisstearamide, 2% of zinc stearate and 1.5% of dioctyl phthalate.
[0102] This embodiment provides a method for preparing the above-mentioned manganese-zinc power ferrite composite material, which comprises the following steps:
[0103] (1) Banburying: Weigh the components of the binder according to the formula, mix to obtain a binder composition, and mix it with the manganese-zinc power ferrite soft magnetic material; raise the temperature of the banbury mixer to 220° C. for preheating, and add the manganese-zinc power ferrite soft magnetic material and the binder composition in sequence after preheating; first, premix at a speed of 10 r / min and press for 20 min, then increase the speed to 25 r / min and mix for 10 min, then increase the speed to 40 r / min, and banbury and keep warm for 40 min to obtain the first material;
[0104] (2) adding the first material into a granulator, extruding and granulating at 160° C. to obtain a second material having a length of 2-3 mm;
[0105] (3) subjecting the second material to injection molding, and forming a magnetic ring blank with a size of Φ16 mm×Φ9 mm×8 mm and a magnetic strip blank with a height of 8 mm through a mold at 80° C.;
[0106] (4) placing the magnetic ring green body and the magnetic strip green body in an oxalic acid degreasing furnace, performing a degreasing treatment at 130° C. and an acid feeding amount of 1 g / min to obtain a degreased green body;
[0107] (5) The debinded blank is first sintered in a nitrogen-oxygen mixed gas (the volume content of oxygen is 21 vol%) at 1290° C. for 5 h, then sintered in a nitrogen-oxygen mixed gas (the volume content of oxygen is 5 vol%) at 1290° C. for 4 h, and finally cooled under a balanced oxygen partial pressure to obtain a manganese-zinc power ferrite magnetic ring composite material and a manganese-zinc power ferrite magnetic strip composite material.
[0108] Example 6
[0109] The difference between this embodiment and Embodiment 2 is that the manganese-zinc power ferrite composite material is made of the following components in weight percentage: 81.7% of manganese-zinc power ferrite soft magnetic material (average particle size of 1.1 μm, water content ≤0.1%) and 18.3% of a binder composition; the binder composition is composed of the following components in weight percentage: 10% of polyoxymethylene resin, 2% of high-density polyethylene, 1% of polyethylene-octene co-elastomer, 0.3% of vinyl bisstearamide, 3% of zinc stearate and 2% of dioctyl phthalate, and the rest are the same as in Embodiment 2.
[0110] Example 7
[0111] The difference between this embodiment and Embodiment 2 is that the manganese-zinc power ferrite composite material is made of the following components in weight percentage: 75% of manganese-zinc power ferrite soft magnetic material (average particle size of 1.1 μm, water content ≤0.1%) and 25% of a binder composition; the binder composition is composed of the following components in weight percentage: 15% of polyoxymethylene resin, 5% of high-density polyethylene, 1.5% of polyethylene-octene co-elastomer, 0.5% of vinyl bisstearamide, 2% of zinc stearate and 1% of dioctyl phthalate, and the rest are the same as in Embodiment 2.
[0112] Example 8
[0113] The difference between this embodiment and Embodiment 2 is that the manganese-zinc power ferrite composite material is made of the following components in weight percentage: 85% of manganese-zinc power ferrite soft magnetic material (average particle size of 1.1 μm, water content ≤0.1%) and 15% of a binder composition; the binder composition is composed of the following components in weight percentage: 10% of polyoxymethylene resin, 2% of high-density polyethylene, 0.5% of polyethylene-octene co-elastomer, 0.5% of vinyl bisstearamide, 1% of zinc stearate and 1% of dioctyl phthalate, and the rest are the same as in Embodiment 2.
[0114] Example 9
[0115] The difference between this embodiment and embodiment 2 is that in the preparation method, step (5) directly sintered the debinded blank in a nitrogen and oxygen mixture (the volume content of oxygen is 21 vol%) at 1290°C for 8 hours, and finally cooled under a balanced oxygen partial pressure. The rest is the same as embodiment 2.
[0116] Comparative Example 1
[0117] The difference between this comparative example and Example 2 is that the manganese-zinc power ferrite composite material is prepared from the following components in weight percentage: 80% of manganese-zinc power ferrite soft magnetic material (average particle size of 1.2 μm, water content ≤0.1%) and 20% of a binder composition; the binder composition is composed of the following components in weight percentage: 15% of polyoxymethylene resin, 1% of polyethylene-octene co-elastomer, 0.5% of vinyl bisstearamide, 0.5% of zinc stearate and 3% of dioctyl phthalate; in the preparation method, the mixing temperature is reduced to 180°C, and the mixing time is adjusted to 30 minutes, and the rest is the same as Example 2.
[0118] Comparative Example 2
[0119] The difference between this comparative example and Example 2 is that the manganese-zinc power ferrite composite material is prepared from the following components in weight percentage: 80% of manganese-zinc power ferrite soft magnetic material (average particle size of 1.2 μm, water content ≤0.1%) and 20% of a binder composition; the binder composition is composed of the following components in weight percentage: 13% of polyoxymethylene resin, 2% of high-density polyethylene, 0.5% of vinyl bisstearamide, 2.5% of zinc stearate and 2% of dioctyl phthalate; in the preparation method, the degreased blank is first sintered in a nitrogen-oxygen mixed gas (the volume content of oxygen is 21 vol%) at 1330° C. for 4 h, and then sintered in a nitrogen-oxygen mixed gas (the volume content of oxygen is 5 vol%) at 1330° C. for 3 h, and finally cooled under a balanced oxygen partial pressure, and the rest is the same as Example 2.
[0120] Comparative Example 3
[0121] The difference between this comparative example and Example 2 is that the manganese-zinc power ferrite composite material is made of the following components in weight percentage: 82% of manganese-zinc power ferrite soft magnetic material (average particle size of 1.2 μm, water content ≤0.1%) and 18% of a binder composition; the binder composition is composed of the following components in weight percentage: 14% of polyoxymethylene resin, 2% of high-density polyethylene, 0.5% of polyethylene-octene co-elastomer, 0.5% of zinc stearate and 1% of dioctyl phthalate, and the rest are the same as Example 2.
[0122] Comparative Example 4
[0123] The difference between this comparative example and Example 2 is that the manganese-zinc power ferrite composite material is prepared from the following components in weight percentage: 81% of manganese-zinc power ferrite soft magnetic material (average particle size of 1.0 μm, water content ≤0.1%) and 19% of a binder composition; the binder composition is composed of the following components in weight percentage: 14% of polyoxymethylene resin, 1.5% of high-density polyethylene, 1% of polyethylene-octene co-elastomer, 0.5% of vinyl bisstearamide and 2% of dioctyl phthalate, and the rest are the same as Example 2.
[0124] Comparative Example 5
[0125] The difference between this comparative example and Example 2 is that the manganese-zinc power ferrite composite material is made of the following components in weight percentage: 82% of manganese-zinc power ferrite soft magnetic material (average particle size of 1.6 μm, water content ≤0.1%) and 18% of a binder composition; the binder composition is composed of the following components in weight percentage: 12% of polyoxymethylene resin, 2% of high-density polyethylene, 1.4% of polyethylene-octene co-elastomer, 0.8% of vinyl bisstearamide, 0.9% of zinc stearate and 0.9% of dioctyl phthalate, and the rest are the same as Example 2.
[0126] Comparative Example 6
[0127] The difference between this comparative example and Example 2 is that the manganese-zinc power ferrite composite material is made of the following components in weight percentage: 80% of manganese-zinc power ferrite soft magnetic material (average particle size of 1.4 μm, water content ≤0.1%) and 20% of a binder composition; the binder composition is composed of the following components in weight percentage: 13.5% of polyoxymethylene resin, 2% of high-density polyethylene, 1.5% of polyethylene-octene co-elastomer, 0.5% of vinyl bisstearamide, 1% of zinc stearate and 1.5% of dioctyl phthalate, and the rest are the same as Example 2.
[0128] Comparative Example 7
[0129] The difference between this comparative example and Example 2 is that the manganese-zinc power ferrite composite material is prepared from the following components in weight percentage: 76% of manganese-zinc power ferrite soft magnetic material (average particle size of 1.2 μm, water content ≤0.1%) and 24% of a binder composition; the binder composition is composed of the following components in weight percentage: 14% of polyoxymethylene resin, 3% of high-density polyethylene, 3% of polyethylene-octene co-elastomer, 0.5% of vinyl bisstearamide, 2.5% of zinc stearate and 1% of dioctyl phthalate, and the rest are the same as Example 2.
[0130] Comparative Example 8
[0131] The difference between this comparative example and Example 2 is that the manganese-zinc power ferrite composite material is prepared from the following components in weight percentage: 73% of manganese-zinc power ferrite soft magnetic material (average particle size of 1.2 μm, water content ≤0.1%) and 27% of a binder composition; the binder composition is composed of the following components in weight percentage: 14% of polyoxymethylene resin, 8% of high-density polyethylene, 1% of polyethylene-octene co-elastomer, 0.5% of vinyl bisstearamide, 2.5% of zinc stearate and 1% of dioctyl phthalate, and the rest are the same as Example 2.
[0132] Test conditions
[0133] The manganese-zinc power ferrite magnetic ring composite materials and the manganese-zinc power ferrite magnetic strip composite materials provided in Examples 1 to 9 and Comparative Examples 1 to 8 were subjected to performance tests, and the test methods are as follows:
[0134] The magnetic properties of Φ16mm×Φ9mm×8mm magnetic ring composite material can be measured by impedance analyzer, SY8218 and SY8258 instruments, such as magnetic permeability, saturation magnetic induction intensity (Bs) and power loss (Pc). The compressive strength of the magnetic strip composite material can be evaluated by a universal testing machine. The measurement diagram is shown in the figure. Figure 2 shown.
[0135] The specific compositions of the manganese-zinc power ferrite magnetic ring composite material and the manganese-zinc power ferrite magnetic strip composite material provided in the embodiments and comparative examples are shown in Table 1:
[0136] Table 1
[0137]
[0138]
[0139] The performance data of the Φ16mm×Φ9mm×8mm magnetic ring composite material and the 8mm high magnetic strip composite material prepared in the embodiments and comparative examples are shown in Table 2.
[0140] Table 2
[0141]
[0142] It can be seen from Table 2 that, compared with the comparative example, the injection molding performance of the manganese-zinc power ferrite composite material provided in the embodiment of the present invention is improved by adjusting the composition of the binder and improving the process conditions, thereby ensuring that it has high magnetic induction intensity (Bs), low power loss (Pc) and good mechanical strength.
[0143] In Example 5, due to the high mixing temperature, part of the polyoxymethylene resin (POM) was oxidized and decomposed at high temperature, resulting in poor mixing effect of the material. The actual sintered density was only 4.4 g / cm 3 There are many pores inside, and the overall porosity of the product is large, which causes the power loss of the manganese-zinc power ferrite magnetic ring composite material to be large and the saturation magnetic induction intensity to be low.
[0144] Compared with Example 2, step (5) in Example 9 adopts a single calcination treatment method of sintering directly in a nitrogen-oxygen mixture (the volume content of oxygen is 21 vol%) at 1290°C for 8 hours, and the comprehensive performance of the manganese-zinc power ferrite composite material finally prepared is deteriorated.
[0145] Comparative Example 1 shows that since no high-density polyethylene component is added to the adhesive composition, the magnetic properties and mechanical strength of the product are reduced.
[0146] Comparative Example 2 shows that due to the lack of polyethylene-octene co-elastomer component in the adhesive composition, the overall compressive strength of the material is low, and no connection points are formed in the molecular structure of the composite material, making it impossible for the system to disperse and buffer pressure well under pressure, so the compressive strength of the product is low.
[0147] Comparative Example 4 shows that the present invention adopts an ultrafine manganese-zinc power ferrite soft magnetic material feeding system, but because it does not add a stearic acid component, the distribution uniformity of the powder particles is poor, resulting in poor compatibility between the manganese-zinc power ferrite soft magnetic material powder and the binder composition, and the overall performance of the obtained product is poor.
[0148] Comparative Examples 5 and 6, as well as Comparative Examples 7 and 8, show that since the content range of some components in the binder composition is not within the preferred range, the comprehensive performance of the prepared magnetic ring composite material and magnetic strip composite material is unbalanced.
[0149] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A manganese-zinc power ferrite composite material, characterized in that: The manganese-zinc power ferrite composite material is made of the following components in weight percentage: 75% to 90% of manganese-zinc power ferrite material and 10% to 25% of a binder composition; The adhesive composition is composed of the following components in weight percentage: 10% to 15% of polyoxymethylene resin, 2% to 5% of high-density polyethylene, 0.5% to 1.5% of polyethylene-octene co-elastomer, 0.2% to 0.5% of vinyl bisstearamide, 1% to 3% of zinc stearate and 1% to 3% of dioctyl phthalate.
2. The manganese-zinc power ferrite composite material according to claim 1, characterized in that: The manganese-zinc power ferrite composite material is made of the following components in weight percentage: 78% to 85% of manganese-zinc power ferrite material and 15% to 22% of a binder composition; Preferably, the adhesive composition is composed of the following components in weight percentage: 10% to 14% polyoxymethylene resin, 2% to 3% high-density polyethylene, 1% to 1.5% polyethylene-octene co-elastomer, 0.3% to 0.5% vinyl bisstearamide, 2% to 3% zinc stearate and 1% to 2% dioctyl phthalate.
3. The manganese-zinc power ferrite composite material according to claim 1 or 2, characterized in that: The average particle size of the manganese-zinc power ferrite material is 1.1-1.4 μm.
4. The manganese-zinc power ferrite composite material according to any one of claims 1 to 3, characterized in that: The melt index of the polyoxymethylene resin is 90 to 150 g / 10 min, preferably 120 g / 10 min.
5. The manganese-zinc power ferrite composite material according to any one of claims 1 to 4, characterized in that: The molecular weight of the high-density polyethylene is 40,000 to 300,000, preferably 100,000; Preferably, the melt index of the high-density polyethylene is 0.1 to 10 g / 10 min, preferably 0.5 g / 10 min.
6. The manganese-zinc power ferrite composite material according to any one of claims 1 to 5, characterized in that: The molecular weight of the polyethylene octene co-elastomer is 3000-3500, preferably 3500; Preferably, the melt index of the polyethylene-octene co-elastomer is 0.1 to 3 g / 10 min, preferably 1.2 g / 10 min.
7. A method for preparing the manganese-zinc power ferrite composite material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: Mixing and kneading the manganese-zinc power ferrite material and the binder composition according to the formula amount to obtain a first material; Extruding and granulating the first material to obtain a second material; The second material is subjected to injection molding to obtain a green body; Degreasing the green body to obtain a degreased body; The degreased blank is sintered to obtain the manganese-zinc power ferrite composite material.
8. The method according to claim 7, characterized in that The preparation method of the manganese-zinc power ferrite material comprises the following steps: subjecting iron oxide, manganese oxide and zinc oxide to a primary ball milling process to obtain a primary ball milling material; subjecting the primary ball milling material to a pre-sintering process to obtain a pre-sintering material; subjecting the pre-sintering material to a secondary ball milling process to obtain the manganese-zinc power ferrite material; Preferably, the mass ratio of the iron oxide, manganese oxide and zinc oxide is 73.4:21.8:4.8; Preferably, the pre-sintering treatment is performed at a temperature of 600 to 900° C. and for a time of 2 to 4 hours; Preferably, the secondary ball milling process further includes drying and sieving processes; Preferably, the water content of the manganese-zinc power ferrite material is ≤0.1%.
9. The method according to claim 7 or 8, characterized in that: The temperature of the banburying is 160°C to 190°C, preferably 180°C to 190°C; Preferably, the banburying time is 30 min to 60 min, preferably 30 min to 45 min; Preferably, the temperature of the granulation treatment is 150°C to 170°C, preferably 150°C to 160°C; Preferably, the length of the second material is 3 to 5 mm; Preferably, the temperature of the injection molding process is 80°C to 140°C.
10. The method according to any one of claims 7 to 9, characterized in that: The degreasing treatment temperature is 100-200°C, preferably 120-150°C; Preferably, the degreasing treatment uses oxalic acid for degreasing; Preferably, the oxalic acid feed rate is 1 to 5 g / min, preferably 1 to 3 g / min; Preferably, the sintering treatment temperature is 1250°C to 1350°C, and the time is 4 to 12 hours; Preferably, the volume content of oxygen during the sintering process is 2 to 21 vol%; Preferably, the sintering process includes first sintering at 1280-1330°C for 5-8h under the condition of an oxygen volume content of 19-21vol%, then sintering at 1280-1330°C for 1-4h under the condition of an oxygen volume content of 2-5vol%, and finally cooling under a balanced oxygen partial pressure.
Citation Information
Patent Citations
Feed material for injection-molding ferrite core formation and preparation method thereof
CN104725034A
Acid degreasing adhesive for powder injection molding and preparation method thereof
CN110280768A
Binder composition, microwave dielectric ceramic granules, ceramic and ceramic filter
CN114685160A
Preparation method of manganese zinc ferrite magnetic spacer
CN115772031A
Feed for ferrite injection molding and preparation method and application thereof
CN116120048A
Cited By
MnZn ferrite feed for injection molding, preparation method of MnZn ferrite feed, magnetic core and preparation method of magnetic core
CN120413222A
